Development of nursing professionalization elements in Slovenia - Skela-Savič, Brigita (Obzornik zdravstvene nege, 2017)
Introduction: An occupation becomes a profession once it uses a systematic approach to generate new knowledge and transfer it directly into professional work. The aim of this paper is to show the attitudes of nursing care professionals towards the professionalization of nursing care and make a contribution by means of identifying the factors that are important for the development of the professionalization of nursing in Slovenia. Methods: The group interview technique was used with two rounds. Participants responded to 15 open premises/questions. Purposive sampling was used and groups were comprised of professionals from all levels of clinical environments, secondary and higher education teachers and master's and doctoral degree students (n = 48). Results: The results of the first round produced 3 themes, while the second round generated findings related to 4 themes. The synthesis of the findings from both rounds resulted in two overarching themes. The first is "National responsibility" which includes the responsibility of the nursing care management and the management of higher education institutions as well as the responsibility of the Nurses and Midwives Association of Slovenia for developing nursing care as a scientific discipline. The second theme is "National indicators for the realization of national responsibility" which includes (1) Classification of jobs in nursing care to reflect the 4 levels of nursing care competencies, (2) research and development as work tools in nursing care, and (3) the national institute for nursing care research. Discussion and conclusion: The responsibility for the development of professionalization lies with several sectors. A clear and ambitious vision, and a strategy for the development of nursing care that should include responsibility for setting a new paradigm for the development of nursing care as a response to the needs of the society, occupation and science, are needed. The strategy should be supported by means of a planned distribution of means to facilitate its realisation.
Keywords: competencies; kompetence; management; menedžment; raziskovanje; research; science; sistematizacija; systematization; znanost